An influence of interval hypoxic training on physical readiness indicators of trained mountaineers - Andrii Kyiko; Viacheslav Mulyk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: determine the influence of interval hypoxic training (IHT) on the indices of physical preparedness at the stage of precompetitive preparation for overcoming Mount Elbrus. Material & Methods: to determine the level of manifestation of physical qualities, the exercises recommended for the training of climbers and methods of mathematical statistics with the calculation of well-known indicators were used to establish the correlation dependence and the reliable difference between the group indices. Results: the conducted studies made it possible to establish that the use of the regime of discontinuous hypoxia 15-15 with breathing through the system into a closed space in the training process of the precompetitive period contribute to an increase in the indices of physical fitness of climbers. Conclusion: the results of the conducted studies indicate that the use of IHT in the 15-15 mode in the period before the ascent to the city of Elbrus allows to significantly increasing the indices of physical preparedness (mainly exercises with a delay in breathing) and the anaerobic and aerobic endurance of skilled climbers in the pre-competition stage.